2000
DOI: 10.1088/0967-3334/21/1/301
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of modified Howland circuits as current generators with current mirror type circuits

Abstract: Multi-frequency electrical impedance tomography (EIT) systems require stable voltage controlled current generators that will work over a wide frequency range and with a large variation in load impedance. In this paper we compare the performance of two commonly used designs: the first is a modified Howland circuit whilst the second is based on a current mirror. The output current and the output impedance of both circuits were determined through PSPICE simulation and through measurement. Both circuits were stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…The output impedance of the implemented current sources has been measured with the impedance analyzer LCR HP4192A in Gain/Phase measurement mode, applying the technique used by Bertemes-Filho in (P. Bertemes-Filho et al 2000). The obtained measurement results have been compared with the calculated values resulting from the output impedance analysis.…”
Section: Output Impedance Measurementsmentioning
confidence: 99%
“…The output impedance of the implemented current sources has been measured with the impedance analyzer LCR HP4192A in Gain/Phase measurement mode, applying the technique used by Bertemes-Filho in (P. Bertemes-Filho et al 2000). The obtained measurement results have been compared with the calculated values resulting from the output impedance analysis.…”
Section: Output Impedance Measurementsmentioning
confidence: 99%
“…It can be concluded that small Z out has a phase near zero or −180 degrees, as the resistors are combined to give a higher Z out and then the phase tends to −90 degrees, as shown in Equation (16) by assuming that the Equation (17) is satisfied.…”
Section: Model 2: Finite Open-loop Gainmentioning
confidence: 99%
“…In most publications, the analysis of the circuit is based on either simplified ideal opamp circuits or using simulation tools, e.g. PSpice or Multisim from NI [12,16]. In many cases, however, the formulas they used are not suitable because the calculation errors are too large with a high-frequency current source [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As current source, the well-known modified Howland circuit was employed [17]. This is a typical circuit to apply in bio-impedance measurements, such as impedance spectroscopy, and multi-frequency electrical impedance tomography [18].…”
Section: A Sinusoidal Oscillatormentioning
confidence: 99%